Leaching of copper from chalcopyrite concentrate by using ammonium persulphate in an autoclave: Determination of most suitable impeller type by using response surface methodology - Turan, M. D.; Altundogan, H. S. (Journal of Central South Univ Technology, 2013)
Some effective parameters on the copper extraction from Kure chalcopyrite concentrate were optimized by using response surface methodology (RSM). Experiments designed by RSM were carried out in the presence of ammonium persulfate (APS) and different types of impeller in an autoclave system. Ammonium persulfate concentration and leaching temperature were defined numerically and three types of impellers were defined categorically as independent variables using experimental design software. The optimum condition for copper extraction from the chalcopyrite concentrate is found to be ammonium persulfate concentration of 277.77 kg/m(3), leaching temperature of 389.98 K and wheel type of impeller. The proposed model equation using RSM has shown good agreement with the experimental data, with correlation coefficients R (2) and R (adj) (2) for the model as 0.89 and 0.84, respectively.
Keywords: copper; chalcopyrite; leaching; response surface methodology; ammonium persulfate; optimization